Waviness of beech sliced veneer - Gornik Bučar, Dominika (Acta silvae et ligni, 2016)
In wood industry, decorative veneer is a product of high added value. Although the technological process of sliced veneer is well known, its quality and price depend on many technological parameters of production, particularly on the quality of logs. The research, which was focused on the influence of visual defects of beech (Fagus sylvatica L.) logs and the impact of climatic conditions in the drying phase of sliced veneer on the surface veneer waviness, was conducted in an industrial environment. The results indicate that the largest share of waved veneer was cut from cracked logs (71%) and less from curved logs (20%). The veneer was sorted manually by experienced controllers from this branch of industry. Their subjective criteria can affect the accuracy of classification of veneer and, consequently, the research results. Therefore, the possibility of using 3D camera for measuring veneer waviness and grading the veneer into quality classes was examined.
Keywords: bukev; Fagus sylvatica; beech; rezani furnir; sliced veneer; sušenje; quality; kakovost; drying; valovitost; waviness; 3D measuring; 3D meritve